Synthesis, Characterization and Biological Activity of Some Novel Formazan Derivatives - Narendra Babu, A.; Rao Nadendla, Rama (Asian Journal of Chemistry, 2010)
1-Substituted phenyl-3-substituted phenyl-4-(o-carboxyphenyl) formazans [3a-s] were synthesized by treating azomethines (A1-5) with diazonium salts. Compounds (A1-5) were synthesized by condensing anthranilic acid with various substituted aromatic aldehydes. All the synthesized compounds were characterized by IR, 1H NMR, Mass and elemental analysis and then evaluated for analgesic, antiinflammatory, antibacterial and antifungal activities.